1993
DOI: 10.1111/j.1365-2842.1993.tb01614.x
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue and EMG changes in the masseter and temporalis muscles during sustained contractions

Abstract: Local muscle fatigue was investigated in the anterior temporal and masseter muscles during sustained isometric contractions. The volunteers' subjective perception of fatigue or pain was recorded at intervals during the sustained contractions, and this level was then compared to objective measures of fatigue. These objective measures included shift in median frequency of the power spectrum of the surface-detected EMG signal, and change in signal amplitude. The relationship was investigated while closing on a bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 9 publications
2
23
0
1
Order By: Relevance
“…Use of a lower pressure level (i.e., with a bite block) would be expected to result in longer endurance times, but the opposite finding occurred. Others have cautioned against detailed interpretations of endurance trials when strength varies substantially across experimental conditions (Lyons et al, 1993;Ward, Theodoros, Murdoch, & Silburn, 2000), but the specific impact of the absolute pressure level at which the endurance trial is performed is unknown and did not affect the present results in the predicted direction.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Use of a lower pressure level (i.e., with a bite block) would be expected to result in longer endurance times, but the opposite finding occurred. Others have cautioned against detailed interpretations of endurance trials when strength varies substantially across experimental conditions (Lyons et al, 1993;Ward, Theodoros, Murdoch, & Silburn, 2000), but the specific impact of the absolute pressure level at which the endurance trial is performed is unknown and did not affect the present results in the predicted direction.…”
Section: Discussionmentioning
confidence: 83%
“…In addition, it is based on only one endurance trial in the bite block condition whereas the jaw-free result was the better of two trials. High trial-to-trial variability has been reported for endurance tasks (Lambert, Archer, & Evans, 2001;Lyons, Rouse, & Baxendale, 1993;Vøllestad, 1997;Walamies & Turjanmaa, 1993). Selecting the best performance from multiple endurance trials would improve task validity, but this strategy is complicated by the fact that the task itself can induce fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that sustained isometric contractions produce a shift of the mean power frequency to lower values. An increase in power at lower frequencies and a decrease in power at higher frequencies have also been observed [10][11][12][13][14][15]. Because of the fatigueinduced shifts in the spectra of sEMG, this technique allows the evaluation of which muscles are most affected by an exercise.…”
Section: Author Manuscript Author Manuscriptmentioning
confidence: 99%
“…The overall goal of this project was to begin to refine the exercise by use of objective indices of fatigue. Surface EMG is used as a clinical tool in the study of skeletal muscle fatigue [10][11][12]. During fatigue, the median (and mean) frequencies of the power spectral density (PSD) function of the sEMG signals shift in a predictable manner [13][14][15].…”
mentioning
confidence: 99%
“…These devices act on the orbicularis oris muscles of the mouth, aiming at its toning and strengthening (7) . However, in literature, little information is available on the prescription of muscle exercises (1) or on the response shown by patients to therapeutic approaches, especially with regard to muscle condition (2,8) . One good example can be found in the recommended time for each exercise, which ranges between 10 seconds (1) , 15-20 seconds (9) , or even 30 seconds of static muscle contractions (7) .…”
Section: Introductionmentioning
confidence: 99%